Atenção plena e sintomas de ansiedade: um estudo correlacional - Lima, Elton Souza de (2022)
Introduction: Mindfulness can be understood as a particular way of connecting with reality, primarily involving the psychic dimensions of consciousness and attention. In this sense, it can be seen as an induced behavioral/emotional state (mindfulness state) or as a subjective predisposition linked to an individual's personality traits (mindfulness trait). In general, studies have shown that the state of mindfulness has a potential inverse relationship with anxiety symptoms. However, it is still unclear how the dispositional mindfulness is associated with anxiety symptoms in non-clinical samples of the general Brazilian population, which is the main theoretical and methodological gap that this study seeks to fill. Objective: To verify if there is a correlation between the level of mindfulness trait and anxiety symptoms in a sample of the general Brazilian population over 18 years of age, who do not have a diagnosed psychiatric disorder, who do not use psychotropic drugs and are not undergoing psychological counseling. Method: This is an analytical, correlational, cross-sectional epidemiological study, carried out online, with the participation of 136 people from the general Brazilian population. An online form was used as a data collection instrument, consisting of three different questionnaires: a) Sociodemographic Questionnaire, b) Beck Anxiety Inventory (BAI) and c) Mindful Attention Awareness Scale (MAAS). Results and discussion: The results presented in this study demonstrate a moderate, inverse and statistically significant association between anxiety symptoms and the mindfulness trait in a sample of the general Brazilian population (r = -0.481; p < 0.001). The results also showed that anxiety symptoms were inversely related to the age of the participants (r = -0.355; p < 0.001), so that the older the participant was, the lower their anxiety levels. In the same direction, the mindfulness trait was positively related to age (r = 0.236; p = 0.007), so that the higher the age, the higher the level of mindfulness trait in the sample. These results are in line with different studies produced internationally on anxiety and mindfulness, contributing to these areas of research.